Outcome of fetoscopic laser ablation for twin‐to‐twin transfusion syndrome in dichorionic–triamniotic triplets compared with monochorionic–diamniotic twins. (November 2014) - Argoti, P. S.; Papanna, R.; Bebbington, M. W.; Kahlek, N.; Baschat, A.; Johnson, A.; Moise, K. J.
ABSTRACT Objective To compare outcome of dichorionic–triamniotic (DCTA) triplet gestations with that of a paired cohort of monochorionic–diamniotic (MCDA) twin gestations undergoing laser therapy for treatment of twin‐to‐twin transfusion syndrome (TTTS). Methods All DCTA triplets treated at four referral centers between specified dates were included. A matched cohort group of MCDA twin gestations affected by TTTS was used for comparison. Results Sixteen sets of DCTA triplets treated with laser photocoagulation of placental anastomoses were compared with 32 matched sets of MCDA twins. All of the 'singleton' fetuses in the triplet gestations survived to birth and to the end of the neonatal period. There were no differences in single or double survival or the rate of non‐survivors to birth and at age 28 days. A mean 3‐week difference was found in the procedure‐to‐delivery interval in DCTA triplets vs MCDA twins (60 ± 35.8 days vs 83.6 ± 33.2 days; P = 0.029). A mean difference of 3 weeks was also found in the gestational age at delivery in DCTA triplets vs MCDA twins (28.5 ± 3.5 weeks vs 31.9 ± 5 weeks; P = 0.024). A similar post‐laser fetal growth pattern in donors and recipients of both groups was noted. Conclusions DCTA triplet gestations with TTTS have a similar rate of post‐laser survival but deliver earlier than can be expected for twins treated with laser. These findings have potential implications for the risk of prematurity and long‐term outcomes. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.